2013
DOI: 10.1111/mmi.12196
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of the autophosphorylation of enzyme INtr by glutamine and α‐ketoglutarate in Escherichia coli

Abstract: Summary In addition to the phosphoenolpyruvate:sugar phosphotransferase system (sugar PTS), most proteobacteria possess a paralogous system (nitrogen phosphotransferase system, PTSNtr). The first proteins in both pathways are enzymes (enzyme Isugar and enzyme INtr) that can be autophosphorylated by phosphoenolpyruvate. The most striking difference between enzyme Isugar and enzyme INtr is the presence of a GAF domain at the N-terminus of enzyme INtr. Since the PTSNtr was identified in 1995, it has been implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 52 publications
3
56
0
Order By: Relevance
“…Using an in vitro-reconstituted system, they demonstrated that 2-OG and glutamine (signals of the carbon and nitrogen statuses) reciprocally regulate the phosphorylation state of PTS Ntr . Glutamine inhibits EI Ntr autophosphorylation, whereas 2-OG stimulates it, which is consistent with the accumulation of unphosphorylated EIIA Ntr under ammonium-sufficient conditions in vivo (124). The binding sites for glutamine and 2-OG were mapped to the GAF domain of EI Ntr (124).…”
Section: The Regulatory Pts (Pts Ntr )supporting
confidence: 65%
See 3 more Smart Citations
“…Using an in vitro-reconstituted system, they demonstrated that 2-OG and glutamine (signals of the carbon and nitrogen statuses) reciprocally regulate the phosphorylation state of PTS Ntr . Glutamine inhibits EI Ntr autophosphorylation, whereas 2-OG stimulates it, which is consistent with the accumulation of unphosphorylated EIIA Ntr under ammonium-sufficient conditions in vivo (124). The binding sites for glutamine and 2-OG were mapped to the GAF domain of EI Ntr (124).…”
Section: The Regulatory Pts (Pts Ntr )supporting
confidence: 65%
“…Glutamine inhibits EI Ntr autophosphorylation, whereas 2-OG stimulates it, which is consistent with the accumulation of unphosphorylated EIIA Ntr under ammonium-sufficient conditions in vivo (124). The binding sites for glutamine and 2-OG were mapped to the GAF domain of EI Ntr (124). However, glutamine, not 2-OG, was found to bind the GAF domain of EI Ntr from Sinorhizobium meliloti (125).…”
Section: The Regulatory Pts (Pts Ntr )supporting
confidence: 62%
See 2 more Smart Citations
“…Nevertheless, in bacteria also possessing EI, HPr, and sugar-specific EIIB and EIIC components, such as most Enterobacteriaceae, a cross talk between the two types of PTS exists (114,115). The activity of EI Ntr was recently shown to be antagonistically regulated by the metabolic intermediates situated at the intersection between carbon and nitrogen metabolism, namely, ␣-ketoglutarate and glutamine (116). Components of the PTS Ntr are found not only in Enterobacteriaceae but also in many proteobacteria that are devoid of any known EIIB and EIIC components.…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%